2007
DOI: 10.1007/s10152-007-0067-6
|View full text |Cite
|
Sign up to set email alerts
|

Testing for the induction of anti-herbivory defences in four Portuguese macroalgae by direct and water-borne cues of grazing amphipods

Abstract: Herbivory is a key factor in regulating plant biomass, thereby driving ecosystem performance. Algae have developed multiple adaptations to cope with grazers, including morphological and chemical defences. In a series of experiments we investigated whether several species of macroalgae possess anti-herbivore defences and whether these could be regulated to demand, i.e. grazing events. The potential of direct grazing on defence induction was assessed for two brown (Dictyopteris membranacea, Fucus vesiculosus) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Furthermore, the ability to induce anti-herbivory traits in response to grazing by mesoherbivores has been repeatedly shown for different F. vesiculosus populations (e.g. Hemmi et al, 2004;Rohde et al, 2004;Long et al, 2007;Yun et al, 2007;Yun et al, 2012).…”
Section: Introductionmentioning
confidence: 90%
“…Furthermore, the ability to induce anti-herbivory traits in response to grazing by mesoherbivores has been repeatedly shown for different F. vesiculosus populations (e.g. Hemmi et al, 2004;Rohde et al, 2004;Long et al, 2007;Yun et al, 2007;Yun et al, 2012).…”
Section: Introductionmentioning
confidence: 90%
“…However, there is increasing evidence that their contribution to antifeeding or antifouling resistance was overestimated (e.g. Jennings & Steinberg 1997, Toth & Pavia 2002, Deal et al 2003, Jormalainen et al 2003, Kubanek et al 2004, Yun et al 2007). Reports on inhibitory activity of phlorotannins with regard to the proliferation of marine bacteria are rare (Lau & Qian 1997, Iken et al 2009), and we are unaware of any studies investigating how the biofilm formation on a thallus is affected by phlorotannins.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on terrestrial plants provide accumulating support for the hypothesis that plants can sense and exploit information from damaged neighbors (reviewed in Dicke et al 2003;Kost and Heil 2006). While plant to plant communication is less studied in the aquatic environment, induced resistance as a response to waterborne cues originating either from a damaged plant or herbivore itself has been found in some Rohde et al 2004, Macaya et al 2005Díaz et al 2006;Yun et al 2007) but not all cases (Sotka et al 2002;Weidner et al 2004;Rohde and Wahl 2008;Macaya and Thiel 2008). The majority of those studies which demonstrated induced resistance as a response to waterborne cues measured algal consumption in preference bioassays, while only a single study measured phlorotannins, finding an induced increase in response to waterborne cues of herbivory .…”
Section: Introductionmentioning
confidence: 97%
“…Strong temporal variation in grazing pressure suggests that induced resistance may provide a profitable defense strategy for F. vesiculosus. While both herbivorederived and artificial cues have been demonstrated to induce a decrease in the palatability of F. vesiculosus Rohde et al 2004;Yun et al 2007), the role of phlorotannins in induced resistance in F. vesiculosus is still inadequately understood. Firstly, we investigate which cues, i.e., grazing by a natural grazer, grazing of a neighboring alga, the sole presence of a grazer and simulated grazing, trigger induced resistance (measured as decreased palatability) in F. vesiculosus.…”
Section: Introductionmentioning
confidence: 98%